HNF1A G319S variant, active cigarette smoking and incident type 2 diabetes in Aboriginal Canadians: a population-based epidemiological study - Gittelsohn Joel; Connelly Philip W; Cao Henian; Mamakeesick Mary; Harris Stewart B; Hegele Robert A; Ley Sylvia H; Retnakaran Ravi; Zinman Bernard; Hanley Anthony J (BMC, 2011)
Abstract Background In a recent report of large-scale association analysis, a type 2 diabetes susceptibility locus near HNF1A was identified in predominantly European descent populations. A population-specific G319S polymorphism in HNF1A was previously identified in Aboriginal Canadians who have a high prevalence of type 2 diabetes. We aimed to investigate the association of the HNF1A G319S polymorphism with incident type 2 diabetes and to assess whether clinical risk variables for type 2 diabetes influence the association in an Aboriginal population. Methods Of 606 participants who were free of diabetes at baseline in 1993-1995, 540 (89.1%) participated in 10-year follow-up assessments in 2003-2005. Fasting glucose and a 75-g oral glucose tolerance test were obtained to determine incident type 2 diabetes. Participants were genotyped for the HNF1A G319S polymorphism. Interviewers administered questionnaires on smoking behavior. Results The incidence rates of type 2 diabetes were 14.2% (55/388) in major allele homozygotes and 31.2% (29/93) in minor allele carriers (p < 0.001). The HNF1A G319S carrier status was associated with incident type 2 diabetes (odds ratio [OR] 3.78 [95% CI 2.13-6.69]) after adjustment for age, sex, hypertension, triglyceride, HDL cholesterol, and waist circumference. A statistical interaction was observed between HNF1A G319S and baseline active cigarette smoking on the development of type 2 diabetes with similar adjustment (p = 0.006). When participants were stratified by baseline smoking status, HNF1A G319S carriers who were active smokers had increased risk of developing diabetes (OR 6.91 [95% CI 3.38-14.12]), while the association was attenuated to non-significance among non-smokers (1.11 [0.40-3.08]). Conclusions The HNF1A G319S variant is associated with incident type 2 diabetes in Aboriginal Canadians. Furthermore, cigarette smoking appears to amplify incident diabetes risk in carriers of HNF1A G319S.